Modal measurement and identification of hexagonal air cushions. (1st November 2022) - Zhang, Yibei; Zhao, Bing; Hu, Jianhui; Mi, Xiang; Chen, Wujun
Highlights: A modal measurement and identification experiment is proposed for air cushions. The vibration properties of top and bottom layers are simultaneously identified. The first 8 modes of an air cushion have been firstly and successfully identified. Abstract: Air cushions have been widely utilised as roofs and facades for large-span buildings owing to their advantages such as ultra-light weight and aesthetic appearance. The dynamic performance of air cushions, which is a typical fluid-solid interaction problem, is complex, because the top layer, bottom layer, and inner air are highly coupled. However, there is a paucity of effective dynamic experimental studies to test the modal characteristics of entire air cushions. Therefore, in this study, a modal measurement and identification method was developed to simultaneously calculate the dynamic properties of both the top and bottom layers of air cushions. A laser displacement sensor array was employed to record the time-history displacement data at the observation points, and the combined application of the fast Fourier transform (FFT) and stochastic subspace identification (SSI) methods was used for modal identification. A hexagonal air cushion was adopted for testing, and the first eight frequencies and modes were successfully identified. The test results indicated that the first mode shape was significantly different from that of a single-layer foil. The one-wave vibration mode shape appeared after the multi-wave mode shapes, which was a unique phenomenon for air cushions. The frequencies and mode shapes of the top and bottom layers were almost identical. The mode deformation of the two layers can be in the same direction or opposite directions, and the frequencies corresponding to the mode shapes of layers vibrating in the same direction were higher than those of layers vibrating in opposite directions.